Cash Management and Financial Performance in Financial Institutions in Uganda, a Case Study of Pride Microfinance Bank (Ltd) Mbale Branch in Mbale City - Racheal Nambozo (Uganda Christian University, 2025)
Financial sustainability is a critical aspect of microfinance institutions (MFIs), requiring effective liquidity management, cash budgeting, and digital banking solutions. This study examines the impact of these financial strategies at Pride Microfinance Mbale, assessing how they contribute to fiscal discipline, operational efficiency, and profitability. Findings reveal that liquidity monitoring, structured budgeting, and digital banking adoption significantly influence financial performance. 35% of respondents rated liquidity management as having a very high impact, while 60% acknowledged liquidity shortages affecting loan disbursement and operational costs. Monthly cash budgeting (45%) emerged as the most commonly used approach, ensuring financial stability. Furthermore, 90% of respondents confirmed the adoption of digital banking, with electronic funds transfers and mobile banking enhancing transaction efficiency. However, challenges such as cash flow unpredictability, reliance on external funding, cybersecurity risks, and system downtimes affect financial operations. The study recommends strengthening real-time liquidity tracking, optimizing budgeting flexibility, and enhancing digital banking security to ensure long-term financial sustainability. Future research should explore AI-driven financial analytics in liquidity forecasting and comparative studies on digital banking adoption in MFIs, providing deeper insights into technological advancements in financial management.